Knowledge and awareness of food safety among middle school students in Tripoli, Libya - Abuhlega, Thuraya Ahmed; Greesh, Malak Ibrahim (Journal of Patan Academy of Health Sciences, 2021)
Introduction: To protect public health in society, it is imperative to promote good food safety practices by raising awareness and knowledge, especially among school students. This study aimed to assess the food safety knowledge and practices among middle school students in Tripoli, Libya. Methods: The study was conducted through a questionnaire to find out the level of food safety knowledge and practices among randomly selected students from several municipalities in Tripoli city, Libya, from May to November 2019. Approval from the director of the Basic Education Administration was taken. Data were analyzed to determine the association of demographics and the level of knowledge and practices, the correlation between knowledge and practice scores. The data analysis was performed by SPSS. A Chi-square test was used to find out the association. A p<0.05 was considered statistically significant. Results: There was a total of 591 students surveyed. A good level of food safety knowledge was found in 325(55%) and the level of food safety practices was high in 558(94.4%). Only 102(17.3%) of the students always washed their hands before eating in school. There was a significant association (p<0.05) between gender and municipality with the knowledge scores. conclusion: The level of food safety practices was high but only half of the middle school students surveyed had a good level of knowledge.